Clonal micropropagation of plants of Aglaonema Schoot - A.N. Lavrentyeva; N.A. Denisyevskaya (Інтродукція Рослин, 1999)
Data about micropropagation of genus Aglaonema Schoot, family Araceae Juss. is cited. Conditions to obtain sterile culture and to determine optimal explant have been developed. Optimal nutrient medium and conditions of meristem plants cultivation are selected.